Pengaruh Foreign Direct Investmet, Produk Domestik Bruto dan Indeks Pembangunan Manusia terhadap Tingkat Pengangguran dengan Inflasi Sebagai Variabel Moderating - Zuha Musnida, Aimma; Nur Asiyah, Binti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research is motivated by the problem of unemployment which is the scourge of developing countries as for developing countries included in the D-8 members of the Organization of Islamic Cooperation (OIC), namely Bangladesh, Egypt, Indonesia, Iran, Malaysia, Nigeria, Pakistan and Turkey. The objectives of this study are to examine the effect of Foreign Direct Investmen, Gross Domestic Product, and Human Development Index on the unemployment rate in 8 OIC member countries and with inflation as a moderating variable. This study used a quantitative approach of assosiative type. The data in this study is sourced from secondary data in the form of annual report and official websites of 8 OIC Memvers States for 2012-2021. Technical data analysis using Eviews 10 with panel data regression test. The result of this study show that: (1) Foreigen Direct Investment has a negative and insignificant effect on the unemployment rate, (2) Gross Domestic Product has a negative and significant effect on the unemployment rate, (3) Human Development Index has a positive and significant effect on the unemployment rate, (4) Foreign Direct Investment strengthened by inflation affects the unemployment rate, (5) Gross Domestic Product strengthened by inflation affects the rate unemployment, (6) The Human Development Index is not reinforced by inflation affecting the unemployment rate.